Factors Influencing ASN Professionality Index Achievements - Prasetyo, Yuda Dwi; Wardani, Ratna (Health Gate, 2024)
State Civil Service employees at the executive level and staff in the service sector still believe that the superior's assessment is the main thing, while other dimensions are not needed. For this reason, it is necessary to search for data on the factors that influence the achievement of the professionalism index for the State Civil Service. The literature search method was carried out based on articles published between 2018-2023 according to the inclusion and exclusion criteria that had been determined using 1 data base, namely Google Schoolar. This literature search uses the PRISMA guideline in carrying out the screening process. From the search results, 1,910 articles were obtained, after the screening process there were 5 articles that met the criteria and analysis would be carried out. The results of the study from 2 literature showed that the factors that influence the achievement of the ASN professionalism index are Content of Policy and Context of Policy, so it can be concluded The State Civil Apparatus Professionalism Index is an indicator of ASN professionalism which can dynamically change along with the achievements achieved by the State Civil Apparatus. Regulations, policies from leadership, resources and the willingness to change from Civil Apparatus Professionalism play an important role in this achievement.Keyword : Professionalism Index, Civil Apparatus Professionalism